How changes in white matter might underlie improved reaction time due to practice. Issue 2 (3rd April 2017) - Voelker, Pascale; Piscopo, Denise; Weible, Aldis P.; Lynch, Gary; Rothbart, Mary K.; Posner, Michael I.; Niell, Cristopher M.
ABSTRACT: Why does training on a task reduce the reaction time for performing it? New research points to changes in white matter pathways as one likely mechanism. These pathways connect remote brain areas involved in performing the task. Genetic variations may be involved in individual differences in the extent of this improvement. If white matter change is involved in improved reaction time with training, it may point the way toward understanding where and how generalization occurs. We examine the hypothesis that brain pathways shared by different tasks may result in improved performance of cognitive tasks remote from the training.